2020
DOI: 10.3390/ma13061306
|View full text |Cite
|
Sign up to set email alerts
|

New Zr-Ti-Nb Alloy for Medical Application: Development, Chemical and Mechanical Properties, and Biocompatibility

Abstract: The concept of mechanical biocompatibilities is considered an important factor for orthopedics and dental implants. The high Young modulus of traditional Ti-based alloys can lead to stress-shielding syndrome and late postoperative complications. The development of new Al- and V-free Ti alloys with a low elastic modulus is a critical task for implantology. Despite the relatively low Young modulus and appropriate biological response of metastable beta-Ti alloys, their production requires complex metallurgical so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 27 publications
3
23
0
1
Order By: Relevance
“…No significant differences in the mitochondrial activity of cells cultured on TNZTS and Ti-6Al-4V were recorded. These results are in agreement with those reported in many studies on the biocompatibility of Ti-based alloys [26,53,54]. Mishchenko et al [53] found that the values of resazurin reduction obtained for human osteoblasts cultured on commercially pure (cp) Ti specimens were not significantly different from those for Zr-Ti-Nb alloy specimens, at each time point, including 24 h. Similarly, employing MC3T3-E1 pre-osteoblasts, cytotoxicity data of 24 h cell culture did not differ significantly between cells grown on cp Ti and Ti-Nb alloys, with Nb contents of 5, 10, 15, 20, and 25 wt./wt.% [26].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No significant differences in the mitochondrial activity of cells cultured on TNZTS and Ti-6Al-4V were recorded. These results are in agreement with those reported in many studies on the biocompatibility of Ti-based alloys [26,53,54]. Mishchenko et al [53] found that the values of resazurin reduction obtained for human osteoblasts cultured on commercially pure (cp) Ti specimens were not significantly different from those for Zr-Ti-Nb alloy specimens, at each time point, including 24 h. Similarly, employing MC3T3-E1 pre-osteoblasts, cytotoxicity data of 24 h cell culture did not differ significantly between cells grown on cp Ti and Ti-Nb alloys, with Nb contents of 5, 10, 15, 20, and 25 wt./wt.% [26].…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with those reported in many studies on the biocompatibility of Ti-based alloys [26,53,54]. Mishchenko et al [53] found that the values of resazurin reduction obtained for human osteoblasts cultured on commercially pure (cp) Ti specimens were not significantly different from those for Zr-Ti-Nb alloy specimens, at each time point, including 24 h. Similarly, employing MC3T3-E1 pre-osteoblasts, cytotoxicity data of 24 h cell culture did not differ significantly between cells grown on cp Ti and Ti-Nb alloys, with Nb contents of 5, 10, 15, 20, and 25 wt./wt.% [26]. Falanga et al [54] showed a similar rate of short-term proliferation and viability of human fibroblast cultured on specimens of Ti-based alloys, including a Ti-Nb alloy.…”
Section: Discussionsupporting
confidence: 93%
“…Серед цих матеріалів слід відзначити широку гаму однофазних сплавів на базі титану, цирконію, ніобію, гафнію, танталу, що дозволяють знизити модуль нормальної пружності до 47-60 ГПа за умови межі міцності від 980 МПа до 1485 МПа. Перевагою зазначених матеріалів є хороша біосумісність і відсутність токсичності для клітин [11]. Проте за даними сплавів обмежена кількість порівняльних оцінок за механічними властивостями і технологічності отримання порівняно з наявними сплавами.…”
Section: аналіз публікаційunclassified
“…Several current investigations are focused on zirconium as a very attractive alternative substitute to titanium in dental implantology [7]. It was reported that zirconium-niobium (Zr-Nb) alloys possessed better corrosion resistance and similar biocompatibility compared to Ti-6Al-4V and pure Ti [8,9]. Moreover, some new studies have shown that bacteria attached to zirconium implants poorly compared to titanium ones [10].…”
Section: Introductionmentioning
confidence: 99%